2009
DOI: 10.1021/bm900113z
|View full text |Cite
|
Sign up to set email alerts
|

Folding, Self-Assembly, and Bulk Material Properties of a De Novo Designed Three-Stranded β-Sheet Hydrogel

Abstract: A de novo designed three-stranded beta-sheet (TSS1) has been prepared that undergoes temperature-induced folding and self-assembly to afford a network of beta-sheet rich fibrils that constitutes a mechanically rigid hydrogel. Circular dichroism and infrared spectroscopies show that TSS1 folds and self-assembles into a beta-sheet secondary structure in response to temperature. Rheological measurements show that the resulting hydrogels are mechanically rigid [at pH 9, G' = 1750-9000 Pa, and at pH 7.4, G' = 8500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 94 publications
(181 reference statements)
1
75
0
1
Order By: Relevance
“…Pochan and Schneider have demonstrated that short amphiphilic peptides that fold into β-hairpin structures will self-assemble into injectable hydrogels that can be used for tissue engineering [236][237][238][239][240][241][242][243][244][245]. The 20-amino acid peptide is composed of two sequences of alternating valine and lysine residues, which have a high propensity for β-sheet formation, adjoining a strong β-turn forming tetrapeptide (-V D PPT-).…”
Section: De Novo Designed β-Hairpin Polypeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pochan and Schneider have demonstrated that short amphiphilic peptides that fold into β-hairpin structures will self-assemble into injectable hydrogels that can be used for tissue engineering [236][237][238][239][240][241][242][243][244][245]. The 20-amino acid peptide is composed of two sequences of alternating valine and lysine residues, which have a high propensity for β-sheet formation, adjoining a strong β-turn forming tetrapeptide (-V D PPT-).…”
Section: De Novo Designed β-Hairpin Polypeptidesmentioning
confidence: 99%
“…The 20-amino acid peptide is composed of two sequences of alternating valine and lysine residues, which have a high propensity for β-sheet formation, adjoining a strong β-turn forming tetrapeptide (-V D PPT-). The molecule is induced into an intramolecularly folded β-hairpin structure by various external stimuli including pH [236], temperature [237], salt [238], and light [240,244]. The alternating valine and lysine residues are oriented such that the molecule is amphiphilic and has one polar, lysine-rich face and one nonpolar, valine-rich face.…”
Section: De Novo Designed β-Hairpin Polypeptidesmentioning
confidence: 99%
“…Peptide-based gels are composed of biologically relevant components (amino acids) that are inherently biodegradable and usually non-toxic and non-immunogenic [123]. Additionally, some peptide-based hydrogels are either sheer thinning or gel instantaneously upon injection into the body [124]. These properties allow for syringe injection of materials to a site of interest, avoiding the need for any toxic crosslinkers.…”
Section: Peptide-based Materialsmentioning
confidence: 99%
“…Biocompatible and biodegradable [147][148][149][150][151][152]. The changes in mechanical properties imparted by the addition of PDIPF to PCL could have an effect on bone formation, but that effect is cell type dependent [156].…”
Section: Peptide Hydrogelsmentioning
confidence: 99%